Rooms of Silence at Three Universities in Scandinavia. (29th October 2018) - Christensen, Henrik Reintoft; Høeg, Ida Marie; Kühle, Lene; Nordin, Magdalena
Abstract: In recent decades, a new type of room has been established in public institutions in Europe: the rooms of silence. In this article, rooms of silence at three Scandinavian universities are analyzed with focus on intention, materiality, and use in relation to increased religious diversity in the student population, individualization, and ongoing secularization. This is done by using a typology which distinguishes between individual and collective use and use associated with religious, spiritual, and secular practices. The analyses show that plans and policies for the rooms emphasize stress-reduction and spiritual or secular reflection. The chaplains actively facilitate the shift from collective to more individual use of the rooms. The analyses also show that the restricted materiality of the rooms shapes practices in ways that either hinder collective Muslim prayer or force students to perform prayer as an individual "silent" action.